(untitled) (Nigerian Journal of Technology, 2016)
Metering mechanism is a key component of planters that directly affect crop development and yield based on the performance of the particular design. Vertical plate metering device is intended to minimize seed damage during planting while improving metering efficiency and field capacity. A vertical plate maize seed planter which is adapted for gardens and small holder farmers cultivating less than two hectares has been designed, constructed and tested. The major components of the planter are hopper, seed metering mechanism, seed chute, furrow opener, furrow closer and wheels. Field test was carried out to determine the field efficiency, effective field capacity, metering efficiency and time required to plant one hectare of farmland. Results showed that the planter has a metering efficiency of 88.94%, effective field capacity of 0.27ha/hr and field efficiency of 71.86%.The time required to plant one hectare of farmland was determined as 3.7 hours. The average number of seeds planted per stand was determined as two and percentage seed damage was determined as 1.71%. This planter is considered economical, requiring no special skill to operate and can be adopted for maize planting by small holder farmers. http://dx.doi.org/10.4314/njt.v35i3.25